A case for enhancing environmental education programs in schools: Reflecting on primary school students’ knowledge and attitudes - Treagust, David; Amarant, A.; Chandrasegaran, Chandra; Won, Mihye (Look Academic Publishers, 2016)
© 2016 Treagust et al. Environmental education in schools is of increasing importance as the world population increases with the subsequent demand on resources and the potential for increased pollution. In an effort to enhance the standing of environmental education in the school curriculum, this study was designed to determine primary students’ knowledge about the environment, their attitudes towards helping the environment and what they actually have done to help the environment. The Year 4 and 5 students in regular and gifted classes in one primary school answered a questionnaire called the Children’s Environmental Attitude and Knowledge Scale (CHEAKS) and several students in both Year levels were interviewed in pairs to elaborate on their responses. In the interviews, students discussed what they had been taught in school in relation to the environment. The findings include (1) Year 4 students had a higher commitment to the environment than Year 5 students; (2) gifted students had more knowledge than regular students; and (3) girls were more verbally committed to the environment than boys. Having knowledge about the environment did not necessarily mean that the student was committed to saving the environment, nor did it mean that the student took action to solve environmental problems. While this study was conducted in one school, the implication is the need for the implementation of a curriculum to help students develop their knowledge and attitudes to take proenvironmental actions.